Application of Android-Based Interactive Multimedia and Local Wisdom on non-fiction text material for Fourth Grade students - Lia Dwi Hartati; Rian Damariswara; Kukuh Andri Aka (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
This research is motivated by the incomplete understanding of students in non-fiction text material because the teacher only uses the lecture method in delivering the material. The purpose of this study was to determine the increase in student learning outcomes in non-fiction text material using interactive media non-fiction texts in Kediri Raya. The method used in this research is Classroom Action Research with 2 cycles of learning with the stages of planning, implementing action, observing, and reflecting. The results of this study have shown an increase in student learning outcomes in the first cycle with an average of 83.18 and the percentage of completeness in the first cycle of 86.36% and this increased in the second cycle obtained an average of 94.54 and the percentage of completeness in the second cycle value is 100%. Thus, it can be concluded that learning non-fiction text stories through interactive media of non-fiction texts in Kediri Raya can improve the learning outcomes of fourth grade students of MI Assalafiyah Pule Kediri.Keywords: Learning outcomes, non-fiction texts, interactive media non-fiction texts of Kediri Raya.